Software technology : methods and tools : 51st international conference, TOOLS 2019, Innopolis, Russia, October 15-17, 2019, proceedings /: methods and tools : 51st international conference, TOOLS 2019, Innopolis, Russia, October 15-17, 2019, proceedings. (2019) - Unknown
No abstract available